2021
DOI: 10.1021/acs.joc.1c01845
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Cascade Formation of Intermolecular C–N Bonds Accessing Substituted Isoindolinones under Cathodic Reduction

Abstract: An electrochemical protocol for the construction of substituted isoindolinones via reduction/amidation of 2-carboxybenzaldehydes and amines has been realized. Under metal-free and external-reductant-free electrolytic conditions, the reaction achieves the cascade formation of intermolecular C−N bonds and provides a series of isoindolinones in moderate to good yields. The deuteriumlabeling experiment proves that the hydrogen in the methylene of the product is mainly provided by H 2 O in the system. I soindolinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…10 Herein, we are interested in the synthetic pathways for isoindolinones and their fused analogues from available starting materials that do not contain any isoindolinone scaffolds in the initial step. Although there is a greater number of reports available on transition-metal catalyzed reactions 11 a – g via the reduction of the number of reaction steps to obtain the most available isoindolinone-based structures, transition metal-free protocols 12–53 offer various advantages over transformations involving transition metal catalysts. Transition metal-catalyzed protocols have the following drawbacks: (a) most metals are very sensitive to air and moisture, (b) toxic metals can easily mixed with drainage water during work-up, and (c) the high cost of metal catalysts is another barrier in the pharmaceutical industry.…”
Section: Literature Reports On the Synthesis Of Isoindolinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Herein, we are interested in the synthetic pathways for isoindolinones and their fused analogues from available starting materials that do not contain any isoindolinone scaffolds in the initial step. Although there is a greater number of reports available on transition-metal catalyzed reactions 11 a – g via the reduction of the number of reaction steps to obtain the most available isoindolinone-based structures, transition metal-free protocols 12–53 offer various advantages over transformations involving transition metal catalysts. Transition metal-catalyzed protocols have the following drawbacks: (a) most metals are very sensitive to air and moisture, (b) toxic metals can easily mixed with drainage water during work-up, and (c) the high cost of metal catalysts is another barrier in the pharmaceutical industry.…”
Section: Literature Reports On the Synthesis Of Isoindolinonesmentioning
confidence: 99%
“…Owing to the importance of C–N bond formation in the synthesis of heterocycles, isoindolinones were synthesized via the electrochemical method from 2-carboxybenzaldehydes 158 and arylamines 159 (Scheme 45). 52 This electrochemical technique was initially checked with an undivided cell equipped with graphite rods as the anode and cathode, using n Bu 4 NHSO 4 as the electrolyte and DMF as the solvent under a constant current of 8 mA in the presence of 2-carboxybenzaldehydes and aniline. The yields of the desired products diminished in ethanol or DMSO solvents and with Pt as the anode instead of a carbon anode.…”
Section: Literature Reports On the Synthesis Of Isoindolinonesmentioning
confidence: 99%
“…Thus, aiming for the application of ortho-formyl acids, in recent years, a number of works have been published. For example, new protocols for the synthesis of 3-difluoroalkyl phthalides [1], 3-benzylphthalides [2], 3-(1 -indolyl)phthalides [3], and electrochemical protocol for isoindolinones [4] were developed. Syntheses of (+)-Rubellin C [5], benzo[f]pyrrolo [1, 2-a] [1,4] diazepines [6], fluorinated isocoumarines [7], furo [2,3-d]pyridazines [8], furo [3,4-c]pyridines [9], 1-oxo-9H-thiopyrano [3,4-b]indoles [10], pyrazoloisoindoles [11], phthalazines [12] and isothiocoumarines [13] were studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, new protocols for the synthesis of 3-difluoroalkyl phthalides [1], 3-benzylphthalides [2], 3-(1 -indolyl)phthalides [3], and electrochemical protocol for isoindolinones [4] were developed. Syntheses of (+)-Rubellin C [5], benzo[f]pyrrolo [1, 2-a] [1,4] diazepines [6], fluorinated isocoumarines [7], furo [2,3-d]pyridazines [8], furo [3,4-c]pyridines [9], 1-oxo-9H-thiopyrano [3,4-b]indoles [10], pyrazoloisoindoles [11], phthalazines [12] and isothiocoumarines [13] were studied. ortho-Formyl acids were used for the synthesis of biologically active compounds with anticancer potential [14]; PROTACs E3 ubiquitin ligase inhibitor [15] and MDM2 [16] degrades; STING [17] and PKM2 [18] modulators; inhibitors of Eg5 [19], SIRT1 and SIRT2 [20], 15lipoxygenase-1 [21] and pyruvate kinase activators [22].…”
Section: Introductionmentioning
confidence: 99%
“… As a powerful synthetic tool, electrochemical synthesis has provided an efficient alternative for reduction reactions because molecules can be activated on a cathode surface with the electron as a reductant . With our continuing interest in cathodic reactions, herein we propose an efficient and safe cathodic reduction strategy for the regioselective coupling of aliphatic ketones with multiple challenging alkenes, affording various tertiary alcohols with different regioselectivities (Scheme c). In our study, we found that zinc salts accumulated on the graphite rod cathode and are speculated to possess an additional interaction with the CC bonds of alkenes by π-bonding, resulting in the double-bond shift of allylarenes .…”
mentioning
confidence: 99%